NUMERICAL METHODS FOR SOLVING DYNAMIC PROBLEMS - Togaev Anvar Abdusalomovich (International Journal of Innovations in Engineering Research and Technology, 2021)
In the article the analysis of methods of the central difference, Newmark, Wilson and Houbolt on a concrete example is resulted. The mathematical model of a test problem is resulted. For the decision of a test problem the program of numerical calculation by means of program MATLAB 7.11.0 (R2010b) is developed and realized. Average deviations of results of calculation from results of the exact decision have made for the central difference method - 2 %, Newmark method of 3,5 %, Wilson method of 5 % and Houbolt method of 6 %. The Most exact decisions give methods of the central difference and Newmark which can be used at calculations of durability of framing.